Alexa duckeana (Leguminosae-Papilionoideae): a new species from the Brazilian Amazon - Silva, Guilherme Sousa Da; Marland Torke, Benjamin; Mansano, Vidal De Freitas (Phytotaxa, 2023)
Alexa (Leguminosae, Papilionoideae) comprises nine species of Amazonian trees. An updated analysis of morphological variation in the genus indicated that material identified as Alexa grandiflora in herbaria constituted two distinct species, one of which appeared to be new. Subsequent fieldwork further supported the distinction. Here, we describe the new species, Alexa duckeana, which differs from A. grandiflora, most notably by lacking extrafloral glands and by having shorter pedicels and shorter racemes with more congested flowers. Alexa duckeana occurs only in the southeastern region of Pará, in northern Brazil. We assess its conservation status as Endangered. In addition to the description, we provide an illustration and distribution map for the new species, taxonomic comparisons, and an identification key for the species of Alexa that occur in Brazil.